Strategi Indonesia Dalam Menangani Pandemi Covid-19 Melalui Foreign Policy and Global Health Initiatives Tahun 2020 - Alfiana Nur Az Zahra; Laode Muhamad Fathun; Garcia Krisnando Nathanael (President University, 2023)
Health diplomacy is carried out by various countries in the world to overcome the Covid-19 pandemic, especially Indonesia through Foreign Policy and Global Health (FPGH) Initiatives by 2020. The concept of global health diplomacy and health security is used to analyze the research problem. The method used in this research is descriptive qualitative using three stages of data analysis, namely data condensation, data presentation, and conclusion drawing and verification. The results shows that the diplomacy carried out by Indonesia through FPGH in 2020 aims to create affordable health access and ensure the availability of vaccines as one of the steps to accelerate the pandemic. Covid-19 consciously increases the ability of countries to collaborate in dealing with the impact of inequality and gap by involving multilateral cooperation as the main factor in realizing health security. These activities are demonstrated through international meetings such as the UN General Assembly, WHO, WHA, and ASEAN and involve the COVAX Facility to ensure fair and equal distribution of vaccines.